Educational museum action - characteristics and possibilities of development - Laszlo Klemar, Kosjenka (Array, 2020)
On the occasion of observing International Museum Day, Croatian museums carry out the Educational Museum Action (EMA) by conducting educational activities - most often workshops, guided tours and didactic exhibitions - on a specific topic set by a museum-leader. Ethnographic museums in Croatia have participated in the Action from the very beginning; in 2000 and 2010, Ethnographic Museum in Zagreb was the leader of the Educational Museum Action. This paper presents a research of EMA features as an educational museum action conducted by analysis of printed booklets as the Action program publications and by responses of museum experts who took part in the organization and implementation of the Action, obtained as a result of a survey. The research points out the discrepancy between the name and features of the organized activity, upon which a state and potentials of the Action development, as well as the museum’s educational activities have been questioned. Curators of ethnographic collections and museum educators in Croatian ethnographic museums, having participated in the research, gave their contribution to determination of issues related to museum educational programs and to determination of their development potentials.